Dividend tax changes and ex-dividend behaviour: the case of South Africa - Chinhema, Michelle (Department of Finance and Tax, 2016)
In April 2012, South Africa changed its tax system on dividends. South Africa switched from using Secondary Tax on Companies (STC) to Dividend Withholding Tax (DWT) in an effort to align with the international standards and eliminate the perception of a higher tax rate. This paper attempts to establish the role of taxes in determining the ex-dividend day share price movements by comparing the pre-tax change and post-tax change in price drop ratio (PDR). In this study, I compare the mean and median PDR before and after the April 2012 Act using a t-test and Wilcoxon Mann Whitney test respectively. Furthermore, this study employs a fixed effects regression model to analyse the PDR change on the ex-dividend day before and after the April 2012 Act. The advantage of using a fixed effects model is that it controls for omitted time-invariant predictors so that the model is not biased because of omitted characteristics. I find a significant difference in the mean and median PDR before and after the tax change. Furthermore, I find that ex-dividend prices vary systematically with taxes as predicted by Elton & Gruber (1970:68) hence supporting the tax-based explanation for ex-dividend day prices. This research is particularly interesting because this is the first tax clientele study in South Africa and the 2012 Act provides a natural experiment where the tax effect can be isolated more effectively compared with other studies that have been done before. Furthermore, this research spans over a narrow time frame thereby reducing the effect of other factors that may also drive ex-dividend day prices.